2017
DOI: 10.1158/1541-7786.mcr-16-0136
|View full text |Cite
|
Sign up to set email alerts
|

High-Affinity Internalizing Human scFv-Fc Antibody for Targeting FGFR1-Overexpressing Lung Cancer

Abstract: Targeted delivery of anticancer drugs using antibodies specific for tumor-associated antigens represents one of the most important approaches in current immuno-oncology research. Fibroblast growth factor receptor 1 (FGFR1) has been demonstrated to be a high-frequency targetable oncogene specific for smokingassociated lung cancers, present in over 20% of lung squamous cell carcinoma cases. This report describes the generation of a potent, fully human antibody fragment in scFv-Fc format efficiently targeting FGF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 47 publications
2
53
0
Order By: Relevance
“…We have recently reported a phage display‐based selection of high‐affinity antibody fragments that selectively recognize epitopes within the D1 domain of the FGFR1 [25]. Furthermore, we have demonstrated that the bivalency and the high affinity promote internalization of FGFR1/engineered antibody complexes [5,6,49].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently reported a phage display‐based selection of high‐affinity antibody fragments that selectively recognize epitopes within the D1 domain of the FGFR1 [25]. Furthermore, we have demonstrated that the bivalency and the high affinity promote internalization of FGFR1/engineered antibody complexes [5,6,49].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in our study we used previously reported bivalent anti‐FGFR1 engineered antibody, B‐Fc, composed of single scFv fused with the Fc (Fig. 1A) [25]. Both proteins were efficiently overproduced in CHO cells and purified using affinity chromatography (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transferrin (Tf) is a well-known plasma protein responsible for transporting iron into cells via the transferrin receptor (TfR) that binds to the cell membrane [20][21][22]. TfR is overexpressed in many human tumors, and it is possible to improve the uptake e ciency of liver cancer cells by transferrin [23][24][25][26]. Transferrin receptors are present on the membrane of liver parenchyma, mannose receptors are distributed on non-parenchymal membranes, and low-density lipoprotein is regulated [27][28][29].…”
Section: Introductionmentioning
confidence: 99%